Perlindungan Hak Anak dalam Sistem Pendidikan di Indonesia - Fazila, Athifa Farras; Yasmin, Nadhifa Aulia; Sijabat, Margaretha Happy Dianezra; Kristianto, Hanny; Manik, Akesia Gracetimansia Br Ginting; Siahaan, Nur Octorise; Yusuf, Nisrina Kamiliya; Silaen, Novenli; Cahayo, Raul Gindo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article analyzes the national legal framework related to the protection of children in conflict with the law and assesses the effectiveness of the application of restorative justice and diversion approaches in the juvenile criminal justice system. The analysis shows that the paradigm of punishment for children has shifted from a retributive approach to a more rehabilitative and restorative approach that emphasizes recovery and the best interests of the child. In the juvenile justice system, trials must be conducted in special closed courts as a form of child privacy protection. Legal proceedings against children emphasize the principle of restorative justice, which focuses more on restoring the child's condition than on punishment, so that diversion efforts become a priority. The handling of children in legal proceedings must not deprive them of their basic rights, especially the right to education. Criminal sanctions for children are educational and rehabilitative in nature, not punitive. Institutions such as prisons, correctional facilities, and juvenile detention centers organize programs aimed at developing children's social skills so that they can resume their social functions with dignity. Thus, legal protection for children in conflict with the law is geared toward promoting the welfare, rehabilitation, and future of the child. Legal protection for children in conflict with the law emphasizes the fulfillment of children's rights as stipulated in the Convention on the Rights of the Child, including the right to protection, education, non-discrimination, and affection. Juvenile court proceedings must be conducted in closed court and use a restorative justice approach that prioritizes rehabilitation and diversion as alternatives to criminal prosecution. Sanctions for children are educational and rehabilitative in nature, not punitive. Through the role of institutions such as prisons, probation offices, and child rehabilitation centers, children are guided so that they can resume their social functions and develop into dignified individuals.